The Poetess - Brockhaus, Stefanie; Wolff, Andy; Tempel, Tobias; Brockhaus, Stefanie; von Schönburg, Christoph; Zenke, Sebastian (Germany : CAT&Docs, 2017)
Hissa Hilal is the voice from behind the veil. Her weapon is her word. Hissa is a self-taught writer and she says what she thinks. She decides to take part an Abu-Dhabi based TV show, “Million’s Poet”. It is the Arab world’s biggest poetry competition, and it is dominated by men, but Hissa becomes the first woman in the finals. In her poems she criticizes patriarchal society and attacks one of the most notorious Saudi clerics for his extremist fatwas, live, in front of 75 million viewers. Yet, we never see Hissa’s face; like the majority of Saudi women, she is covered from head to toe. How did she gain the knowledge and courage to step on stage and risk her life?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films